Quantum-dot cellular automata serial decimal processing-in-wire: Run-time reconfigurable wiring approach. (September 2016) - Gladshtein, Michael
Abstract: The quantum-dot cellular automata (QCA) technology is promising to overcome the limits of CMOS technology for perspective computers. A chain of QCA is used as a wire. Logic gates are simply implemented by a cross pattern of QCA. Because the leading role of QCA wires, the serial data transfer/processing is preferable. The growing market of financial, Internet-based, and automatic control computer applications requires a binary-coded decimal data encoding for direct processing of decimal information without representation and conversion errors. The 5-bit decimal Johnson–Mobius encoding and radical departure from Boolean logic allow using a delay element, implemented by short length of QCA wire, as a function element. The previous published by author serial decimal QCA arithmetic designs demonstrate hardware simplification in comparison with traditional designs. The paper presents novel serial decimal adder and adder/subtractor designs used the run-time reconfigurable wiring approach, which results in further significant QCA hardware simplification.